A standardized framework to evaluate the quality of studies using TDABC in healthcare: the TDABC in Healthcare Consortium Consensus Statement - Ana Paula Beck da Silva Etges; Carisi Anne Polanczyk; Richard D. Urman (BMC, 2020)
Abstract Background This Consensus Statement introduces a standardized framework, in a checklist format, to support future development and reporting of TDABC studies in healthcare, and to encourage their reproducibility. Additionally, it establishes the first formal networking of TDABC researchers through the creation of the TDABC in Healthcare Consortium. Methods A consensus group of researchers reviewed the most relevant TDABC studies available in Medline and Scopus databases to identify the initial elements of the checklist. Using a Focus Group process, each element received a recommendation regarding where in the scientific article section it should be placed and whether the element was required or suggested. A questionnaire was circulated with expert researchers in the field to provide additional recommendations regarding the content of the checklist and the strength of recommendation for each included element. Results The TDABC standardized framework includes 32 elements, provides recommendations where in the scientific article to include each element, and comments on the strength of each recommendation. All 32 elements were validated, with 21 elements classified as mandatory and 11 as suggested but not mandatory. Conclusions This is the first standardized framework to support the development and reporting of TDABC research in healthcare and to stablish a community of experts in TDABC methodology. We expect that it can contribute to scale strategies that would result in cost-savings outcomes and in value-oriented strategies that can be adopted in healthcare systems and institutions.